2005
DOI: 10.1016/j.jtcvs.2004.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of survival of transplanted smooth muscle cells with real-time polymerase chain reaction

Abstract: One hour after implantation, only 50% of smooth muscle cells remained in the implanted area. Some implanted cells deposited in other tissue. Implanted cell survival progressively decreased during the 4-week study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 24 publications
5
51
0
1
Order By: Relevance
“…We chose biochemical strategies rather than a histological assay, because of the potential for high precision and rapid turnaround [13,38,41,88]. (We recognize the loss of structural information using biochemistry, but this can be obtained in follow up validation studies.)…”
Section: Development Of Rapid Assays For Graft Sizementioning
confidence: 99%
See 2 more Smart Citations
“…We chose biochemical strategies rather than a histological assay, because of the potential for high precision and rapid turnaround [13,38,41,88]. (We recognize the loss of structural information using biochemistry, but this can be obtained in follow up validation studies.)…”
Section: Development Of Rapid Assays For Graft Sizementioning
confidence: 99%
“…These studies showed that a panoply of cells injected into the myocardium both can change the nature of the scar and improve post-infarction cardiac function. Skeletal myoblasts [6][7][8], fetal or neonatal cardiomyocytes [9][10][11], fibroblasts [12], smooth muscle cells [13], hematopoietic stem cells [14,15], mesenchymal stem cells [16], endothelial cells [17], resident cardiac progenitor cells [18,19], and derivatives of human embryonic stem cells [20][21][22][23][24] have all been transplanted into animal hearts. While it is clear that functional benefit is conferred from numerous cell types, the mechanism of action is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogels were also shown to exhibit high cell encapsulation efficiencies, supporting cell viability over a one week culture period. These results suggest that the materials appear to be promising to investigate as cell carriers in regenerative medicine approaches, for instance as vehicles to deliver smooth muscle cells for myocardium cell therapy 26 and chondrocyte for cartilage regeneration, 27 although evaluation of specific cell types for cytocompatibility evaluation would be necessary.…”
Section: Hydrogel Degradation and Cytocompatibilitymentioning
confidence: 99%
“…12, 14 Briefly, DNA of the whole hearts from groups M, M + R, and M + R + AG (n=4 animals per group) was extracted using the Genomic DNA Purification Kit (Promega), and the concentration of the purified DNA was determined by spectrophotometry. The specific primers were designed according to the GeneBank sequences of the sex-determining region of Y-chromosome (SRY) gene of the rat (sense 5'-CATCGAAGGGTTAAAGTGCCA-3', anti-sense 5'-ATA-GTGTGTAGGTTGTTGTCC-3').…”
Section: Analysis Of Donor Cell Marker and Survivalmentioning
confidence: 99%